2010
DOI: 10.1111/j.1467-6427.2010.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual distress and dyadic adjustment over a three‐year follow‐up period in couple therapy: a bi‐directional relationship?

Abstract: This study examined the relationship between depressive symptoms and dyadic adjustment, as well as between interpersonal problems and dyadic adjustment, during residential couple therapy and at a three-year followup (N 5 106). Mixed models were used in the analyses. Significant improvement (po.001) occurred on all measures from admission to discharge (effect sizes .27 À .83) and from admission to three-year followup (effect sizes .52 À .79). During the observation period, improvement in depressive symptoms at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
(75 reference statements)
0
8
1
Order By: Relevance
“…Tilden et al. [31] showed that the improvement of relationship quality can reduce depression. In relation to chronic pain, the Leonard et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tilden et al. [31] showed that the improvement of relationship quality can reduce depression. In relation to chronic pain, the Leonard et al.…”
Section: Introductionmentioning
confidence: 99%
“…Prigerson et al [30] showed that poor relationship quality is related to increases in depression and poor health outcomes. Tilden et al [31] showed that the improvement of relationship quality can reduce depression. In relation to chronic pain, the Leonard et al review [22] calls for a greater understanding of the role of patient mood state on relationship outcome, pain, and disability.…”
Section: Introductionmentioning
confidence: 99%
“…www.FamilyProcess.org treating depressive symptoms (d = À.12) and significantly more effective than individual therapy in alleviating relationship distress (d = À.60). Further, reduction in depressive symptoms has also been replicated in naturalistic studies of couple therapy in different countries (Klann, Hahlweg, Baucom, & Kröger, 2011;Tilden, Gude, Hoffart, & Sexton, 2010).…”
Section: Efficacy Of Interventions For Intimate Partner Relationship mentioning
confidence: 81%
“…Although assessment of a couple‐level outcome may be a good fit here, and a great next step in this line of work, it is believed that there is importance in understanding the influence of the shared alliance on one of the most common outcomes of therapy—individual level of distress. Furthermore, individual levels of distress are often highly intertwined with couple‐level functioning and couple‐level therapy outcomes (Knobloch‐Fedders, Pinsof, & Haase, 2015; Tilden, Gude, Hoffart, & Sexton, 2010). Therefore, individual levels of distress seem to be an appropriate barometer of therapy outcome, even in the couple context.…”
Section: The Cfm and Couple Therapymentioning
confidence: 99%